Triaging acute pulmonary embolism for home treatment by Hestia or simplified PESI criteria: the HOME-PE randomized trial. (7th August 2021) - Roy, Pierre-Marie; Penaloza, Andrea; Hugli, Olivier; Klok, Frederikus A; Arnoux, Armelle; Elias, Antoine; Couturaud, Francis; Joly, Luc-Marie; Lopez, Raphaëlle; Faber, Laura M; Daoud-Elias, Marie; Planquette, Benjamin; et al.
Abstract: Aims: The aim of this study is to compare the Hestia rule vs. the simplified Pulmonary Embolism Severity Index (sPESI) for triaging patients with acute pulmonary embolism (PE) for home treatment. Methods and results: Normotensive patients with PE of 26 hospitals from France, Belgium, the Netherlands, and Switzerland were randomized to either triaging with Hestia or sPESI. They were designated for home treatment if the triaging tool was negative and if the physician-in-charge, taking into account the patient's opinion, did not consider that hospitalization was required. The main outcomes were the 30-day composite of recurrent venous thrombo-embolism, major bleeding or all-cause death (non-inferiority analysis with 2.5% absolute risk difference as margin), and the rate of patients discharged home within 24 h after randomization (NCT02811237). From January 2017 through July 2019, 1975 patients were included. In the per-protocol population, the primary outcome occurred in 3.82% (34/891) in the Hestia arm and 3.57% (32/896) in the sPESI arm ( P  = 0.004 for non-inferiority). In the intention-to-treat population, 38.4% of the Hestia patients (378/984) were treated at home vs. 36.6% (361/986) of the sPESI patients ( P  = 0.41 for superiority), with a 30-day composite outcome rate of 1.33% (5/375) and 1.11% (4/359), respectively. No recurrent or fatal PE occurred in either home treatment arm. Conclusions: For triaging PE patients, the strategy based on the Hestia rule and the strategy based on sPESI had similar safety and effectiveness. With either tool complemented by the overruling of the physician-in-charge, more than a third of patients were treated at home with a low incidence of complications. Graphical abstract: